The use of triptans as an effective form of migraine treatment – review - Borkowska, Agata; Kiełb, Anna; Mich, Anna; Kaźmierczak, Anna; Sornek, Patrycja; Izdebska, Wiktoria; Pawlak, Igor; Ciesielski, Radosław; Stanek, Jakub; Perkowska, Klaudia (Quality in Sport, 2025)
Introduction Migraine, a prevalent neurological disorder, is characterized by recurrent episodes of moderate to severe headache, often accompanied by symptoms such as nausea, photophobia, and phonophobia. Triptans, which belong to the class of serotonin 5-HT1B/1D receptor agonists, are integral to the management of migraine, providing prompt relief from symptoms. Aim of the study To clarify how effective triptans are in treating migraines, highlighting their role in symptom relief and improving patients’ quality of life Materials and methods The article is the result of a comprehensive analysis of present-day scientific literature, which has been collected from PubMed, Scopus, and Google Scholar. The literature was systematically reviewed utilizing specific keywords. Results Studies consistently show high efficacy of triptans in treating acute migraines. These pharmaceuticals markedly alleviate pain and symptoms like nausea, photophobia, and phonophobia, providing substantial pain relief. Differences in triptan medications’ onset and half-life affect their therapeutic duration and headache recurrence rate. The pharmacokinetic properties of each triptan significantly affect its efficacy and headache recurrence likelihood. Frovatriptan, with its long half-life, showed superior efficacy in reducing migraine recurrence. Conversely, rizatriptan, with its rapid action, offered quick pain relief. In clinical trials, all triptans showed favorable tolerability profiles. Reported adverse effects were generally mild. Conclusions Triptans are effective and safe for managing acute migraines. The diverse formulations and swift onset make these treatments essential for migraine management. Choose a triptan based on efficacy, safety, and patient preferences. More research is needed to improve triptan treatments for migraine, focusing on reducing headache recurrence and enhancing patient tolerability.